Asymmetric phase-transfer catalysts bearing multiple hydrogen-bonding donors: Synthesis and application in nitro-Mannich reaction of isatin-derived N-Boc ketimines. Issue 24 (14th June 2017) - Liu, Yuxin; Liu, Yu; Wang, Jingdong; Wei, Zhonglin; Cao, Jungang; Liang, Dapeng; Lin, Yingjie; Duan, Haifeng
Graphical abstract: Highlights: Synthesized a series of APT catalysts bearing multiple H-bonding donors. First (PTC) system used in this reaction. Good reaction activity and enantioselectivities (yields 96–99%, up to 95% ee). Abstract: A series of bifunctional asymmetric phase-transfer catalysts bearing multiple hydrogen-bonding donors derived from cinchona alkaloids are synthesized, and successfully applied to asymmetric nitro-Mannich of isatin-derived N-Boc ketimines. The products 3-substituted 3-amino-oxindoles were constructed in excellent yields (96–99%) and good enantioselectivities (up to 95% ee).